Versatile Oxidation Methods for Organic and Inorganic Substrates Catalyzed by Platinum‐Group Metals on Carbons. Issue 1 (15th December 2015) - Sawama, Yoshinari; Asai, Shota; Monguchi, Yasunari; Sajiki, Hironao
Abstract: Platinum‐group metals on activated carbon catalysts, represented by Pd/C, Ru/C, Rh/C, etc., are widely utilized to accomplish green and sustainable organic reactions due to their favorable features, such as easy handling, recoverability, and reusability. The efficient oxidation methods of various organic compounds using heterogeneous platinum‐group metals on carbons with or without added oxidants are summarized in this Personal Account. The oxidation of internal alkynes into diketones was effectively catalyzed by Pd/C in the presence of dimethyl sulfoxide and molecular oxygen or pyridine N ‐oxide. The Pd/C‐catalyzed mild combustion of gaseous hydrogen with molecular oxygen provided hydrogen peroxide, which could be directly utilized for the oxidation of sulfide derivatives into sulfoxides. Furthermore, the Ru/C‐catalyzed aerobic oxidation of primary and secondary alcohols gave the corresponding aldehydes and ketones, respectively. On the other hand, the dehydrogenative oxidation of secondary alcohols into ketones was achieved using Rh/C in water, and primary alcohols were effectively dehydrogenated by Pd/C in water under mildly reduced pressure to produce carboxylic acids. Abstract : Various green oxidation techniques catalyzed by heterogeneous platinum‐group metals on carbon are summarized. Platinum‐group metals on carbon successfully catalyzed the oxidations of hydrogen, alkynes, alcohols and sulfides based on the oxygen oxidation or dehydrogenation pathways.